113 Neointimal Coverage of Bioresorbable Vascular Scaffolds within Four Months – Can we Stop Dual Antiplatelets Early?. (6th June 2015) - Giblett, Joel; Brown, Adam; Keevil, Harry; West, Nick; Hoole, Stephen
Abstract : Background: Neointimal strut coverage significantly reduces risk of stent thrombosis, which may allow abbreviated dual anti-platelet therapy if clinically necessary. Optical coherence tomography (OCT) provides unparalleled axial resolution to define strut coverage. We used OCT to assess neointimal strut coverage of Bioresorbable Vascular Scaffolds (BVS) at an earlier timepoint than published studies. Methods: OCT imaging was performed at baseline and 1–4 months post-implantation in patients receiving BVS. OCT scaffold strut coverage (strut thickness >160 μm), mean flow/scaffold area (MFA/MSA) and incomplete strut apposition (ISA) were assessed every 1 mm (n = 865 frames) longitudinally throughout the scaffold. Measures were compared at baseline and follow up. Results: 20 BVS (median 3.0 × 18 mm) were included in the analysis. 90% of patients were male and mean age was 54.4 ± 9.2 yrs. Median follow up was 70 (range 29–112) days. 16 (80%) stented lesions were classified as AHA B2 or C. At follow-up, only 91/3, 280 struts (2.8%) were uncovered. ISA was observed for 60 struts (2.0%) at baseline and 14 struts (0.5%) at follow up (p < 0.05). Only 4 BVS (20%) had ISA at follow-up. MFA reduced from 7.79 mm 2 at baseline to 7.37 mm 2, at follow up (Δ-5.43%, p < 0.05), due to neointimal growth (mean area +1.07 mm 2 ). MSA was not significantly different at follow up (-0.11 mm 2, Δ-1.27%, p = 0.45). Conclusions: BVS exhibited low rates of uncovered struts within four months following implantation. Although MFA had reduced due to neointimal growth, MSA was preserved, implying adequate BVS radial strength despite the complex lesion subset. These data suggest that abbreviated dual-antiplatelet therapy may be possible following BVS implantation if clinically necessary.